Purification and characterization of a 4-hydroxynonenal metabolizing glutathione S-transferase isozyme from bovine pulmonary microvessel endothelial cells - He, Nong-Gao; Singhal, Sharad S; Chaubey, Meena; Awasthi, Sanjay; Zimniak, Piotr; Partridge, Catherine A; Awasthi, Yogesh C (Biochimica et biophysica acta, 1996)
Previous studies have suggested that a group of structurally and immunologically related mammalian glutathione S-transferases (GSTs) which utilize 4-hydroxynonenal (4-HNE) as the preferred substrate and show glutathione peroxidase activity towards phospholipid hydroperoxides may be important for the defense of cells against lipid peroxidation. In present studies we have purified and characterized GST isozymes of bovine pulmonary microvessel endothelial (BPMVE) cells. The results of these studies indicate that BPMVE cells express relatively high amounts of a GST isozyme which utilizes 4-HNE as the preferred substrate. This GST isozyme purified to homogeneity from BPMVE cells showed remarkably high specific activity towards 4-HNE (48.3 units/mg protein) and had similar immunological, kinetic, and structural characteristics as reported for mouse enzyme mGSTA4-4 and other mammalian GSTs of this group. Since the endothelial cells are exposed to constant oxidative stress, we suggest that this GST isozyme may be important for the defense of these cells against lipid peroxidation.